Brain fMRI Predicts Responses to Certolizumab Pegol in RA. an International, Multi-center, Randomized, Double-blind, Placebocontrolled Trial (PreCePRA) - Rech, Jürgen; Schenker, Hannah; Tascilar, Koray; Hagen, Melanie; Kleyer, Arnd; Simon, David; Mendez, Larissa Valor; Schoenau, Verena; Prade, Jutta; Sergeeva, Marina; Sulvakumar, Mageshvar; Strobelt, Sandra; et al. (ARTHRITIS & RHEUMATOLOGY, 2020)
CRIS-Team WoS Importer:2021-01-15

CENTRAL NERVOUS SYSTEM PAIN RESPONSE AND COMPONENTS OF DISEASE ACTIVITY IN RA PATIENTS AFTER TREATMENT WITH CERTOLIZUMAB OR PLACEBO: A POST-HOC ANALYSIS FROM THE PRECEPRA TRIAL - Schenker, Hannah; Rech, Jürgen; Tascilar, K.; Hagen, Melanie; Schoenau, V.; Sergeeva, Marina; Selvakumar, Mageshwar; Konerth, Laura; Prade, Jutta; Strobelt, Sandra; Valor, L.; Hueber, A.; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2020)
CRIS-Team WoS Importer:2020-08-21

Epilepsy-related functional brain network alterations are already present at an early age in the GAERS rat model of genetic absence epilepsy - Wachsmuth, Lydia; Hebbelmann, Leo; Prade, Jutta; Kohnert, Laura C.; Lambers, Henriette; Lüttjohann, Annika; Budde, Thomas; Heß, Andreas; Faber, Cornelius (Frontiers in Neurology, 2024)
Introduction: Genetic Absence Epilepsy Rats from Strasbourg (GAERS) represent a model of genetic generalized epilepsy. The present longitudinal study in GAERS and age-matched non-epileptic controls (NEC) aimed to characterize the epileptic brain network using two functional measures, resting state-functional magnetic resonance imaging (rs-fMRI) and manganese-enhanced MRI (MEMRI) combined with morphometry, and to investigate potential brain network alterations, following long-term seizure activity. Methods: Repeated rs-fMRI measurements at 9.4 T between 3 and 8 months of age were combined with MEMRI at the final time point of the study. We used graph theory analysis to infer community structure and global and local network parameters from rs-fMRI data and compared them to brain region-wise manganese accumulation patterns and deformation-based morphometry (DBM). Results: Functional connectivity (FC) was generally higher in GAERS when compared to NEC. Global network parameters and community structure were similar in NEC and GAERS, suggesting efficiently functioning networks in both strains. No progressive FC changes were observed in epileptic animals. Network-based statistics (NBS) revealed stronger FC within the cortical community, including regions of association and sensorimotor cortex, and with basal ganglia and limbic regions in GAERS, irrespective of age. Higher manganese accumulation in GAERS than in NEC was observed at 8 months of age, consistent with higher overall rs-FC, particularly in sensorimotor cortex and association cortex regions. Functional measures showed less similarity in subcortical regions. Whole brain volumes of 8 months-old GAERS were higher when compared to age-matched NEC, and DBM revealed increased volumes of several association and sensorimotor cortex regions and of the thalamus. Discussion: rs-fMRI, MEMRI, and volumetric data collectively suggest the significance of cortical networks in GAERS, which correlates with an increased fronto-central connectivity in childhood absence epilepsy (CAE). Our findings also verify involvement of basal ganglia and limbic regions. Epilepsy-related network alterations are already present in juvenile animals. Consequently, this early condition seems to play a greater role in dynamic brain function than chronic absence seizures.
CRIS-Team Scopus Importer:2024-03-29
Keywords: absence epilepsy; deformation-based morphometry; functional connectivity; GAERS; graph theory; MEMRI; rs-fMRI; spike–wave-discharges

LONGITUDINAL CHANGE IN THE CENTRAL NERVOUS SYSTEM PAIN RESPONSE AFTER TREATMENT WITH CERTOLIZUMAB OR PLACEBO. A POST-HOC ANALYSIS FROM THE PRECEPRA TRIAL - Rech, Jürgen; Tascilar, K.; Schenker, Hannah; Hagen, Melanie; Sergeeva, Marina; Selvakumar, Mageshwar; Konerth, Laura; Prade, Jutta; Strobelt, Sandra; Schonau, V.; Valor, L.; Hueber, A.; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2020)
CRIS-Team WoS Importer:2020-08-21

Prediction of Response to Certolizumab-Pegol in Rheumatoid Arthritis By Functional MRI of the Brain - an Interim Analysis of an Ongoing Investigator Initiated Phase III Trial - Schenker, Hannah; Heß, Andreas; Konerth, Laura; Sergeeva, Marina; Prade, Jutta; Kleyer, Arnd; Reiser, Michaela; Hueber, Axel; Englbrecht, Matthias; Feist, Eugen; Voll, Reinhard; Bannert, Bettina; et al. (2017)
EVALuna2:33139

Prediction of response to Certolizumab-Pegol in rheumatoid arthritis (PreCePRA) by functional MRI of the brain – Study protocol for a randomized double-blind controlled study - Schenker, Hannah; Tascilar, Koray; Konerth, Laura; Sergeeva, Marina; Prade, Jutta; Strobelt, Sandra; Kleyer, Arnd; Simon, David; Mendez, L.; Hagen, Melanie; Schönau, V.; Hueber, A.; et al. (Contemporary Clinical Trials Communications, 2021)
Background: Tumor necrosis factor inhibitors (TNFi) signify a major advance in the treatment of rheumatoid arthritis (RA). However, treatment success initially remains uncertain as approximately half of the patients do not respond adequately to TNFi. Thus, an unmet need exists to better predict therapeutic outcome of biologicals. Objectives: We investigated whether brain activity associated with arthritis measured by functional magnetic resonance imaging (fMRI) of the brain can serve as a predictor of response to TNFi in RA patients. Methods: PreCePRA is a multi-center, randomized, double-blind, placebo-controlled fMRI trial on patients with RA [1] [2]. Active RA patients failing csDMARDs therapy with a DAS28 > 3.2 and at least three tender and/or swollen joints underwent a brain BOLD (blood-oxygen-level dependent) fMRI scan upon joint compression at screening. Patients were then randomized into a 12-week double-blinded treatment phase with 200 mg Certolizumab Pegol (CZP) every two weeks (arm 1: fMRI BOLD signal activated volume > 2000 voxel, i.e. 2 cm3; arm 2: fMRI BOLD signal activated volume <2000 voxel) or placebo (arm 3). DAS28 low disease activity at 12 weeks was assigned as primary endpoint. A 12-week follow-up phase in which patients were switched from the placebo to the treatment arm followed the blinded phase. fMRI was carried out at screening as well as after 12 and 24 weeks of receiving CZP or placebo. Conclusion: We hypothesize that high-level central nervous representation of pain in patients with rheumatoid arthritis predicts response to the TNFi CZP which we further investigate in the PreCePRA trial.
CRIS-Team Scopus Importer:2021-06-04
Keywords: functional MRI; Neuroimaging; Rheumatoid arthritis; TNF inhibition

PREDICTION OF RESPONSE TO CERTOLIZUMAB PEGOL TREATMENT BY FUNCTIONAL MRI OF THE BRAIN: AN INTERNATIONAL, MULTI-CENTER, RANDOMIZED, DOUBLE-BLIND, PLACEBO-CONTROLLED TRIAL (PRECEPRA) - Rech, Jürgen; Tascilar, K.; Schenker, Hannah; Sergeeva, Marina; Selvakumar, Mageshwar; Konerth, Laura; Prade, Jutta; Strobelt, Sandra; Hagen, Melanie; Schonau, V.; Valor, L.; Hueber, A.; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2020)
CRIS-Team WoS Importer:2020-08-21